THE IMPACT OF DOHA PEACE AGREEMENT ON PAKISTAN - Samiullah; Mazhar Islam; Sanaullah; Shakeel Iqbal; Rafeed Ullah Khan (PalArch’s Journal of Archaeology of Egypt / Egyptology, 2021)
Americans and the Taliban signed a deal, for Bringing Peace in Afghanistan, in Doha on 29 February 2020 to end the war in Afghanistan which Afghanis have suffered for two decades. This study aims to find out the overall impact of the Doha agreement on Pakistan. The study is qualitative in nature by using an exploratory method. On contrast, there are certain spoilers within Afghanistan and in the region that are against peaceful Afghanistan, which could reduce the success chances of this agreement. The Doha peace agreement has very positive repercussions for Pakistan, particularly on its security and trade. Pakistan should continue their support of this peace deal because peace in Afghanistan means peace in Pakistan.